Ultrasound—assisted periareolar oncoplastic approach in breast surgery: a focus on surgical technique - De Luca, Alessandro; Tripodi, Domenico; Fortunato, Lucio; Pediconi, Federica; Cannistrà, Claudio; Rocco, Nicola; Vergine, Massimo; Amabile, Maria Ida (Frontiers in Surgery, 2025)
IntroductionBreast conservation surgery (BCS) combined with post-operative radiotherapy is the standard and preferred treatment for early-stage breast cancer (eBC), offering survival outcomes comparable to mastectomy while improving body image and quality of life. Oncoplastic breast surgery (OBS) has evolved from BCS to allow more extensive tissue removal while maintaining oncological safety and reducing the risk of post-surgical deformities. The ultrasound (US)-assisted periareolar approach in breast surgery offers several potential benefits, including reduced scarring, improved cosmetic outcomes, and enhanced surgical precision, particularly for non-palpable or small lesions, and potentially better nipple sensation preservation. This study aim to describe an US-assisted periareolar OBS approach for eBC patients with small to moderate breast ptosis.MethodsHere we present a focus on surgical technique consisting in OBS combining a US-assisted periareolar approach with volume displacement in small- to moderate- ptosic breasts. Margin resection adequacy, surgical complications and patient satisfaction using the Breast-Q questionnaire were assessed.ResultsThirty-two patients were considered. A negative margin of excision was achieved in all cases, and patients routinely received post-operative hypofractionated radiotherapy. Seroma was the most common complication (12.5%), while breast fat necrosis and minor wound infections occurred in 6% and 3% of cases, respectively. At a median follow-up of 12 months (range 6–18), post-treatment breast retraction occurred in 3 patients (9%), all of whom underwent fat grafting to improve outcomes. The average satisfaction score as determined by Breast-Q module was 78.6, rising to 81.3 for those who underwent contralateral mammaplasty.DiscussionThe combination of imaging, the use of oncoplastic surgical techniques and an appropriate post-operative management may provide the surgeon new tools for the treatment of eBC. In selected cases, the US-assisted periareolar oncoplastic approach is a versatile technique that can be easily adapted for tumors in any location of the breast.